THE APPLICATION OF UNO CARD GAME TO IMPROVE MASTERY OF MATERIAL AL ‘ADAD AL MUFROD AL ‘ASHLI WA AT TARTIBI CLASS X MA BILINGUAL JUNWANGI KRIAN: Penerapan Permainan Kartu UNO untuk Meningkatkan Penguasaan Materi Al ‘Adad Al Mufrod Al ‘Ashli wa At Tartibi Kelas X MA Bilingual Junwangi Krian - Safira Rahmawati Ashari; Najih Anwar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
There are 3 elements in learning Arabic, namely, sound elements (ashwat), vocabulary elements (mufradat) and sentence structure elements (tarkib) and all of them are regulated by Arabic grammar sciences such as, balaghah science, sharaf science, nahwu science. The science of nahwu studies the layout of sentences and the end of the harakat in a word. Some of the nahwu material, one of which is Al 'adad which is found in the discussion of isim or nouns. Based on observations made in class X MA Bilingual Junwangi Krian Sidoarjo, where Al 'adad material is usually taught in a traditional way, boring and lack of innovation, so that students often have difficulty understanding it, it is necessary to use the UNO card game media. The purpose of this study was to determine how the application and improvement of mastery of Al 'Adad Al Mufrod Al 'Ashli wa At Tartibi material by using UNO card game media. The research method used is classroom action research with data collection techniques including; tests, observations, interviews and documentation. The results showed that, first, the application of the UNO card game is guided by the teacher in a group of 5 students, the teacher explains the game procedure, and students start playing cards and give examples of sentences until the card runs out, for habituation, the game is done 2-3 times. Second, the use of UNO card game media can improve the mastery of Al 'Adad A l Mufrod Al ‘Ashli wa At Tartibi with student learning completeness which continues to increase from 50% to 100% and from a value that reaches KKM 85 only 20% to 90%. It can be concluded that there is an effect of the application of UNO card game media to improve mastery of the material Al 'Adad Al Mufrod Al 'Ashli wa At Tartibi.